CHALLENGES AND PROSPECTS OF COVID – 19 ON SAARC MEMBER COUNTRIES - Junaid Ahmed, Dr. Deep Kishore Srivastav (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2019)
The virus that turns on localize shock to China is now delivering a salient shock globally. The noble coronavirus has made the whole environment around the world unstable for the people. The virus has stopped many economic activities due to its contagious effect and till date, no cured has discovered to fight against the coronavirus. The coronavirus has hit the SAARC member countries so badly that it has been revealed by World Bank that these nations have been facing worst economic performance in more than 40 years. This coronavirus has impacted the economy of the SAARC member countries so badly that it has been predicted that these nations can even go into recession in the upcoming future years. Government of these member countries have developed and adopted various policies to combat the effect of the coronavirus pandemic among which the most common were social distancing and country- wide lockdown. This study simulates the potential impact of COVID - 19 on the economy of SAARC member countries. It covers the impact on gross domestic product and trade, international trade costs, international travels, etc. The research also studies the outbreak of coronavirus on the countries from the very first case to the number of cases till 30th June 2020. It covers the measure or policies taken by different nations for regional cooperation and at the individual level to fight the battle of coronavirus pandemic. It was found that the economies were already in the parlous state before the COVID – 19 crises. The prolonging of country-wide lockdown has shown a global economic downturn and also disrupted the demand and supply chains due to which economies are facing a period of slowdown. In this paper, we describe the potential impact of coronavirus pandemic on various segments of the economy, analyse the policies that have been announced by SAARC member countries individually and for the regional cooperation and the future prospect of SAARC after COVID – 19. KEYWORDS: coronavirus (COVID – 19), Lockdown effect, SAARC, economic impact, pandemic, contagious disease, international trade